Transient elastography for noninvasive assessment of liver fibrosis in patients with primary biliary cirrhosis - Alempijevic, Tamara; Copertino, Ana; Boricic, Ivan; Milicic, Biljana; Pavlovic-Markovic, Aleksandra; Krstic, Miodrag; Matovic, Vera; Popovic, Dusan Dj (Vojnosanitetski pregled, 2020)
Backgrund/Aim. In recent decades noninvasive methods for the assessment and monitoring of liver fibrosis have been developed and evaluated in numerous chronic liver diseases. The aim of this study was to evaluate the diagnostic accuracy of noninvasive markers for fibrosis assessment transient elastography (TE) and biochemical markers using liver biopsy as reference in patients with primary biliary cirrhosis (PBC). Methods. One hundred and twenty-two patients underwent both liver biopsy and blood tests on the same day and TE in a month following the biopsy and the tests. Liver biopsies were reviewed by a single pathologist using the METAVIR scoring system for assessment of liver fibrosis. Aspartate aminotransferase (AST), platelet ratio index (APRI), Forns scores, AST and alanine transaminase (ALT) ratio and TE were compared with liver fibrosis stage in order to determine the best noninvasive marker of liver fibrosis. Results. There was a statistically significant difference (p < 0.05) for the APRI score, Forns index and TE according to stages of liver fibrosis. TE showed superior diagnostic performance when compared to other surrogate markers of liver fibrosis that were investigated. Optimal cut-off for TE were 4.25 and 5.9 kPa for diagnosing the presence of fibrosis and distinguishing mild/moderate and advanced stages of fibrosis respectively. The areas under the receiver operating characteristic (AUROC) of TE were 0.963 and 0.865, respectively. Conclusion. Based on our investigation the APRI score, Forns index and TE adequately predict fibrosis stage in patients with primary biliary cirrhosis, but the most sensitive and specific parameter appears to be TE. Using noninvasive markers and methods in the evaluation of patients in daily clinical practice may reduce, but not eliminate, the need for invasive diagnostic procedures.